FLDs on Turmeric (Rajendra sonia) in Muzaffarpur, Bihar: Adoption Horizontal Spread and Satisfaction Level - Meena, M. L.; Singh, Pushpa; Kundu, M. S. (Indian Journal of Extension Education, 2021)
Keeping in view of effective extension approach of Frontline demonstrations (FLDs) forÂ dissemination of technology FLDs on turmeric conducted by KVK, Turki, Bihar. The yieldÂ and economic performance of frontline demonstration, horizontal spread of technology,Â extent of adoption level and extent of satisfaction of respondent farmer over extension services and performance of demonstration was measured. It was observed that there wasÂ 15.0 to 19.6 per cent increase in fresh rhizome yield over local check and the average benefit cost ratio was higher under demonstration 3.3 as compared to control plots 2.5 during the all years of the study. The horizontal spread of turmeric cv. Rajendra sonaliÂ was estimated from about 13 ha during 2015-16 to 43 ha during the year 2019-20. TheÂ findings of the study also revealed that there was increase in adoption level ranging fromÂ 9.4 per cent of sowing time and method to 46.9 per cent of improved and quality seed after the FLD programmes. The majority of the respondent farmers expressed high extentÂ (51.2%) to the medium (34.4%) extent of satisfaction from extension services andÂ performance of technology under demonstrations. It can be concluded that frontline demonstrations are one of the important tool to demonstrate newly released crop production and protection technologies and its management practices in the farmerâ€™s field underÂ different agro-climatic region and farming situations